Analysis of chilean sanitary indicators - Huerta-Riveros, Patricia Carolina; Leyton-Pavez, Carolina Elena; Paúl-Espinoza, Iván Renato (Horizonte Sanitario, 2019)
Objective: Analyze health indicators, based on the results obtained by health establishments in Chile, during the period 2010-2014.Methods and material: A descriptive study is realized and multiple correspondence is applied. 75 basic health indicators published by the Ministry of Health, demographic indicators, vital statistics, health risks and access to care are used. Each indicator was assigned an expected result and compared with the actual result obtained, by region and country.Results: Health risk indicators were characterized mainly because in 50% and more of the analyzed regions they obtained a result similar to the expected result. Unlike the vital statistics indicators, where 49% and less of the regions had a result similar to that expected in the same period. At the same time, the demographic indicators were associated with a positive expected result and, on the contrary, the indicators of access to care were associated with a negative expected result in the period analyzed.Conclusions: Due to the impact on the population, any indicator of health management should be considered by health network managers to guide the strategies to be implemented in the establishments that conform public health care networks. Key words: Health management; Strategy; Management indicators.